Noise Estimation and Reduction in Heart Sounds Using Time Frequency Block Thresholding Method - Vishwanath Shervegar, M.; Bhat, Ganesh V (Asian Journal of Electrical Sciences, 2016)
In this paper a novel method of de-noising phonocardiogram by time-frequency Overlapping Group Shrinkage method is described. In this method sigma, the standard deviation of the stationary noise present in a noisy phonocardiogram is found using activity detection. This noise is then canceled by attenuating it in the time frequency domain. The accuracy of noise reduction is measured by SNR. Overlapping Group shrinkage algorithm reduces the effect of noise by attenuating them using hard or soft thresholding. Performance of this method was found to be far better compared to other methods such as Soft Thresholding and Block Thresholding.